Atom probe tomography of an alkali activated fly ash concrete. (July 2019) - Tuinukuafe, Atolo; Kaub, Tyler; Weiss, Charles A.; Allison, Paul G.; Thompson, Gregory B.; Amirkhanian, Armen
Abstract: The atomic structure of alkali-activated materials (AAMs) is comprised of aluminum and silicon tetrahedral units organized in a manner that is elusive to characterization by many experimental techniques. This letter reports the use of atom probe tomography (APT) to determine the atomistic partitioning of an alkali-activated fly ash, which lends new insights into the nanoscale chemical heterogeneity of the material. APT effectively provides 3D ionic-level resolution of the alkali-activated fly ash examined in this study, and could be useful for the analysis of other cementitious materials or ceramics as well.